PLANT PHOTOTROPISM AS THE BASIS FOR DESIGNING INCLUSIVE LIGHTING IN SPACES FOR THE DEAF - Muhammad Rizqy Akbar; Aghnia Zahrah (Universitas Mercu Buana, 2025)
This article explores a biomimetic architectural approach that applies the concept of plant phototropism as a conceptual foundation for designing inclusive lighting environments for individuals who are deaf or hard of hearing. Recognizing that deaf users rely on visual perception as their primary medium of communication, this study draws an analogy between the way plants move toward light and the way deaf individuals orient themselves within illuminated spaces. Supported by the multisensory theory in architecture (Spence, 2020), which asserts that spatial perception arises from the integration of multiple senses, this research employs qualitative and conceptual experimentation based on plant growth direction to develop lighting design principles that are even, adaptive, and responsive to visual communication needs. These principles are translated into architectural strategies such as the orientation of spaces toward natural light, the balanced distribution of artificial illumination, and the use of material reflectance, positioning phototropism as a biomimetic foundation for DeafSpace development that enhances both functionality and sensory experience.